The edible native Australian fruit, Davidson's plum (Davidsonia pruriens), reduces symptoms in rats with diet-induced metabolic syndrome. (May 2019) - John, Oliver D.; Mouatt, Peter; Prasadam, Indira; Xiao, Yin; Panchal, Sunil K.; Brown, Lindsay
Graphical abstract: Highlights: Davidson's plum is an indigenous Australian fruit rich in anthocyanins. Davidson's plum decreased abdominal fat, adipose cells size and total fat mass. Davidson's plum improved cardiovascular structure and function. Davidson's plum improved liver structure and function. Abstract: Davidson's plum is a native Australian fruit used traditionally as food and medicine. The fruit contains anthocyanins as glucosides and sambubiosides of cyanidin and peonidin (691 mg/100 g of dried pulp) with rutin and quercetin glycosides (193 mg/100 g). Dietary supplementation of Davidson's plum at approximately 8 mg anthocyanins/kg/day in rats attenuated the signs of metabolic syndrome induced by high-carbohydrate, high-fat diet. Davidson's plum reduced visceral fat accumulation, total abdominal fat weight, size of retroperitoneal adipocytes, and plasma triglycerides and non-esterified fatty acids, normalised blood pressure, reduced left ventricular stiffness, decreased infiltration of inflammatory cells in both left ventricle and liver, decreased collagen deposition in heart, and reduced both fat vacuoles in liver and obesity-induced degeneration of knee cartilage. There were no changes in glucose tolerance with treatment. Davidson's plum reduced colonic Clostridiaceae spp, and increased Turicibacter spp. and Akkermansia muciniphila . Our findings indicate that Davidson's plum is a potential complementary treatment for metabolic syndrome.